Schools or markets? : commercialism, privatization, and school-business partnerships - Boyles, Deron (L. Erlbaum Associates, 2005)
This book challenges readers to consider the consequences of commercialism and business influences on and in schools. Critical essays examine the central theme of commercialism via a multiplicity of real-world examples.